2011
DOI: 10.1002/uog.8983
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal nitroglycerin in patients with severe pre‐eclampsia with placental insufficiency: effect on uterine, umbilical and fetal middle cerebral artery resistance indices

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…. According to previous studies, the MCA‐PI remained unaltered following administration of GTN, suggesting that fetal cerebral arterial vascular tone does not depend on external NO supply. The similar results from our study give further support to this observation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…. According to previous studies, the MCA‐PI remained unaltered following administration of GTN, suggesting that fetal cerebral arterial vascular tone does not depend on external NO supply. The similar results from our study give further support to this observation.…”
Section: Discussionsupporting
confidence: 91%
“…Glyceryl trinitrate (nitroglycerin, GTN) produces NO through a biotransformation pathway. A previous study on GTN showed improvement in Doppler indices and maternal blood pressure. One of its limitations is the development of tolerance, which can be reduced by intermittent administration.…”
Section: Introductionmentioning
confidence: 99%
“…NO precursors are represented by L-arginine [35]. Evidence for their role in the prevention and treatment of PE is now emerging, yet deriving from small clinical studies [36,37]. Thus, further research is needed in this field before clinical recommendations could be given.…”
Section: Nitric Oxide Donors and Precursorsmentioning
confidence: 97%
“…They reported an increase of the blood low in the uterine and umbilical arteries. However, further investigation is needed for their efect reducing the incidence of PE [33].…”
Section: No Pathwaymentioning
confidence: 99%